EVALUASI SISTEM PENATAUSAHAAN PENERIMAAN KEUANGAN DAERAH PADA BADAN PENGELOLA KEUANGAN DAN ASET DAERAH (BPKAD) KOTA KENDARI - Intihanah, Intihanah; Tamburaka, Sulvariani; Sari, Dwi Novita (JURNAL AKUNTANSI DAN KEUANGAN, 2017)
ABSTRACTÂ The research aims to determine the financial administration system reception area on Badan Pengelola Keuangan dan Aset Daerah Kendari has been applied in accordance with Regulation No. 21 Year 2011. Data collection techniques used in this study is documentation and interviews . This research uses descriptive analysis methodThe results of this study showed that administration of financial reception area has been equipped with a document SKP / SKR, Certificate of Proof of Payment, Credit Note STS and in accordance with Regulation 21 of 2011. Where, treasurer shall administer the reception had to use a letter of deposit (STS) has been authorized by the Bank and by STS, treasurer reception reports administratively reception.Keyword : Local Finance Revenue, Administration,Evaluation